THE IMPACT OF KARATE EXTRACURRICULAR ON PARENT SATISFACTION IN ISLAMIC ELEMENTARY SCHOOLS - Indah Nurhidayati; Mujiburrohman; Lu’lu’ Fathimah Nursalma (Profetika: Jurnal Studi Islam, 2024)
The problems faced by schools related to karate extracurricular education services are students who are less active and easily bored in karate extracurricular activities. This study aims to find out: 1) Karate extracurricular education services at Fatahillah Sukoharjo Integrated Islamic Elementary School, 2) The influence of karate extracurricular education services on the level of parent satisfaction of students of Fatahillah Sukoharjo Integrated Islamic Elementary School. This study uses a quantitative method. The research was conducted at Fatahillah Sukoharjo Integrated Islamic Elementary School. Data collection techniques by documentation and questionnaire/questionnaire methods. The sampling method used a total sampling of 53 respondents. The data were analyzed using a simple linear regression analysis technique with the help of SPSS V25 software. To test the validity of the data, validity tests, reliability tests, normality tests, and linearity tests were carried out. The results of the study show that: 1) Karate extracurricular education services are in the "adequate" category with a percentage of 47%, 2) Based on the results of the calculation t, 8,905 > from t table 2,006 which means that the influence is significant. Furthermore, it is seen from the calculation of simple linear regression of significance level 0.00 < 0.05 and the calculation of the confusion determination of the influence of karate extracurricular education services on the level of satisfaction of parents of students of Fatahillah Sukoharjo Integrated Islamic Elementary School by 60.9%.